Optimalisasi Pembelajaran Coding Berbasis Kecerdasan Buatan untuk Meningkatkan Literasi Digital Siswa - Wahyuni, Linda; Rizal, Chairul; Rosnelly, Rika; Sari, Rita Novi; Hardianto, Hardianto; Harahap, Charles Bronson (Forum Kerjasama Pendidikan Tinggi, 2026)
This community service program aims to enhance the professional capacity of teachers through mastery of modern educational technologies. The implementation of this program is based on several issues identified within the partner institution, including teachers’ limited understanding of artificial intelligence, their low ability to integrate coding into learning activities, and the suboptimal use of digital tools and media in the classroom. These challenges contribute to students’ low digital literacy and the insufficient application of project-based learning that aligns with current technological developments. The training program was designed to strengthen teachers’ competencies in implementing AI-based coding instruction through participatory approaches and hands-on practice. The learning modules were developed contextually to meet the specific needs of the partner school, enabling teachers to adapt them easily into their teaching practices. The results of the program indicate significant improvements in teachers’ understanding of fundamental AI concepts, their ability to integrate coding into the learning process, and their capacity to apply digital technologies ethically and effectively. Enhanced student engagement was also observed, as learners became more enthusiastic and active in participating in project-based learning activities involving AI applications. Although the program faced several limitations, such as inadequate technological equipment and limited implementation time, it has established a strong foundation for the development of more structured and sustainable follow-up activities. Overall, the outcomes demonstrate that strengthening teachers’ competencies in artificial intelligence plays a crucial role in fostering an innovative digital learning ecosystem aligned with the demands of 21st-century education.